INFLUENCE OF THE PARAMETERS OF THE LASER MARKING PROCESS ON THE DEPTH OF PENETRATION IN LAYER-REINFORCED COMPOSITES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the present study, we track the influence of the change in the energy parameters of a laser installation based on Fiber laser - RFFL-P-502B, on the depth of penetration in marking layer-reinforced polymer-based composites. To determine their influence on the depth of the marked strokes, experiments were carried out at speed V= 50÷250 mm/s, output power P = 5÷50 W, pulse frequency f = 50 kHz and diameter of the focal spot 40μm. Tabular results and graphical dependences of the obtained experimental results are presented..